Dual‐Loaded Liposomes Tagged with Hyaluronic Acid Have Synergistic Effects in Triple‐Negative Breast Cancer. Issue 16 (11th March 2022) - Dong, Shiyan; Bi, Ye; Sun, Xiangshi; Zhao, Yarong; Sun, Rongze; Hao, Fei; Sun, Yating; Wang, Yifan; Li, Xuefeng; Deng, Weiye; Liu, Xuan; Ha, JongHoon; et al.
Abstract: Triple‐negative breast cancer (TNBC) is the most lethal subtypes of breast cancer. Although chemotherapy is considered the most effective strategy for TNBC, most chemotherapeutics in current use are cytotoxic, meaning they target antiproliferative activity but do not inhibit tumor cell metastasis. Here, a TNBC‐specific targeted liposomal formulation of epalrestat (EPS) and doxorubicin (DOX) with synergistic effects on both tumor cell proliferation and metastasis is described. These liposomes are biocompatible and effectively target tumor cells owing to hyaluronic acid (HA) modification on their surface. This active targeting, mediated by CD44‐HA interaction, allows DOX and EPS to be delivered simultaneously to tumor cells in vivo, where they suppress not only TNBC tumor growth and the epithelial‐mesenchymal transition, but also cancer stem cells, which collectively suppress tumor growth and metastasis of TNBC and may also act to prevent relapse of TNBC. Abstract : An actively targeted liposomal formulation of epalrestat and doxorubicin for a triple‐negative breast cancer therapy with synergistic effects on both tumor cell proliferation and metastasis, along with outstanding biocompatibility and excellent tumor targeting ability is presented. These characteristics suggest that such liposomal preparations would be an attractive part of a universal treatment strategy for metastatic tumors.